Divine Medicine: Healing and Charity Through Spirit-Writing in China - Zheng, Qijun (Religions, 2024)
This study traces the evolution of religious healing practices associated with divine presence in China, from pre-modern traditions to the modern use of spirit-writing for obtaining divine prescriptions. It examines the continuity and transformation of these practices from the late imperial period to contemporary times. It argues that healing through divine prescriptions obtained via spirit-writing challenges the perceived dichotomy between religion and science, demonstrating that they have complementary roles, rather than being strictly opposing categories. For members of Jishenghui 濟生會, a lay Buddhist charity devoted to the Buddhist god Jigong 濟公 in Republican China, religion and scientific medical practice were integrated as complementary elements of daily life, combining doctrinal beliefs, ritual practices, and moral self-cultivation. This study examines how Jishenghui used spirit-writing to obtain and distribute divine prescriptions and medicines, demonstrating that the organization’s philanthropic activities and social standing were enhanced by the integration of religious beliefs with medical and charitable practices during the Republican period. This study bridges existing research on the histories of spirit-writing and Chinese medicine, and the distinctions made between “Buddhist medicine” and “Daoist medicine”. The article contends that, for ordinary people, no strict distinction existed between Buddhist and Daoist healing practices; instead, a shared religious culture regarding illness and healing was predominant. By contextualizing key analytical concepts such as “divine medicine”, especially “divine prescriptions” (jifang 乩方 and xianfang 仙方) within the broader history of Chinese medicine and religious practices, this article demonstrates the social significance of spirit-writing as a ritual technique to provide healing and charity by lay Buddhists in Republican China, and its enduring relevance in contemporary Chinese societies.